2015
DOI: 10.1111/1467-8551.12126
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Organizational Performance: A Case for Subjective Measures

Abstract: We review the organizational performance (OP) measurement literature highlighting the limitations of both objective and subjective measures of performance. We argue that, with careful planning, subjective measures can be successfully employed to assess OP. This is because often consistent, reliable and comparable compatible objective data on OP measures – particularly across countries and sectors – is difficult to come by. Considering that an inflated OP measure can be cross‐checked with the use of secondary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
201
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(235 citation statements)
references
References 67 publications
0
201
0
4
Order By: Relevance
“…Finally, all variables used in this study are subjective; however, business scholars have consistently found that such measures lead to results that are not significantly different from those relying on so-called objective variables, as can be seen for instance in Dawes (1999), Wall et al (2004), Singh et al (2016), and Vij and Bedi (2016).…”
Section: Limitations and Future Researchmentioning
confidence: 82%
“…Finally, all variables used in this study are subjective; however, business scholars have consistently found that such measures lead to results that are not significantly different from those relying on so-called objective variables, as can be seen for instance in Dawes (1999), Wall et al (2004), Singh et al (2016), and Vij and Bedi (2016).…”
Section: Limitations and Future Researchmentioning
confidence: 82%
“…Second, subjective performance ratings make it possible to rely on SMEs as a research context in which objective performance data are often not publicly reported. Third, subjective ratings allow for comparable performance assessments in multi‐industry samples like ours where objective performance indicators may not be directly comparable between companies (Singh, Darwish, & Potočnik, ). Fourth, in order to further validate our subjective performance measure, we collected publicly available performance data for as many of the SMEs in our sample as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Singh, Darwish and Potočnik (2016) found that on the basis of evidence from four countries, managerially reported data seemed to be generally an accurate representation of how firms were doing. With survey data, there is also the perpetual bugbear of possible common method variance bias; we would argue that testing for this is a better path to simply rejecting work that carries a whiff of it; however, this view is not shared by a significant proportion of reviewers.…”
Section: Insert Table 3 About Herementioning
confidence: 99%